Peran Filsafat dalam Lembaga Pendidikan Islam: Studi Ontologis di RA Miftahul Huda Bonangrejo dalam Menjawab Problematika Pendidikan Islam Kontemporer - Muarifah, Muarifah; Mujibburrohman, Mujibburrohman (TSAQOFAH, 2025)
This article aims to analyze the role of philosophy in Islamic educational institutions, specifically at RA Mifrahul Huda Bonangrejo, with an emphasis on the ontological approach in Islamic philosophy. The study is grounded in the urgency of strengthening character, ethics, and moral values in early childhood education amidst moral challenges and the globalization of values in the contemporary era. A qualitative approach was employed, utilizing observation and in-depth interviews with three Islamic Religious Education (PAI) teachers. The findings reveal that although philosophy has not been explicitly integrated into the curriculum, an understanding of the fundamental concept of being in Islamic philosophy significantly contributes to instilling transcendental values, spirituality, and morality. These findings underscore the importance of revitalizing the role of Islamic philosophy as a conceptual foundation in Islamic education to address the moral crisis and character degradation among the younger generation. Therefore, integrating an ontological approach into early childhood education practices becomes both relevant and imperative.